Producing composite materials based on ZrB[2], ZrB[2]-SiC; IOP Conference Series: Materials Science and Engineering; Vol. 156 : Materials and Technologies of New Generations in Modern Materials Science - Mirovoi Yu. A.; Burlachenko A. G.; Buyakova S. P. Svetlana Petrovna; Sevostiyanova I. N.; Kulkov S. N. Sergey Nikolaevich (2016, 2016)
Title screen